Financial regulatory transparency: New data and implications for EU policy - Mark Copelovitch; Christopher Gandrud; Mark Hallerberg (Bruegel, 2015)
[Highlights] International financial institutions have promoted financial regulatory transparency, or the publication by supervisors of financial industry data. Financial regulatory transparency enhances market stability and increases democratic legitimacy. We introduce a new index of financial regulatory data transparency - the FRT Index. It measures how countries report to international financial institutions basic macro-prudential data about their financial systems. The Index covers 68 high-income and emerging-market economies over 22 years (1990-2011). We find a number of striking trends over this period. European Union members are generally more opaque than other high-income countries. This finding is especially relevant given efforts to create an EU capital markets union. Globally, financial regulatory data transparency has increased. However, there is considerable variation. Some countries have become significantly more transparent, while others have become much more opaque. Reporting tends to decline during financial crises. We propose that the EU institutions take on a greater role in coordinating and possibly enforcing reporting of bank and non-bank institution data. Similar to the United States, a reporting requirement should be part of any EU general deposit insurance scheme.
Keywords: 330